The future of deliveries: Parcel locker intentions - Fara Adura, Mohd Yusoff; Fazeeda, Mohamad; Puteri Fadzline, Muhamad Tamyez; Siti Aisyah, Panatik
The global expansion of e-commerce and increasing usage of parcel locker has prompted researchers to delve into this field. Thus, this study looked into the variables that encourage automated parcel lockers use among Malaysian consumers. In this study, an additional variable, to change was added to the Unified Theory of Acceptance and Use of Technology (UTAUT). This study is based on quantitative study and applied non-probability sampling technique which is voluntary technique. Data were collected through an online survey (n=423), and analysed using structured equation modeling. The finding found that three factors: performance expectancy, effort expectancy and innovativeness could affect behavioural intention. These findings provide new and additional knowledge about this innovative last-mile delivery intention, and the contributions to the theory and society. This study has explored the applicability of the UTAUT theory to study last-mile delivery in Malaysia, highlighting it theoretical ramifications. Finally, the findings are useful to aid courier companies and other relevant parties in outlining plans and carrying out strategies and initiatives to encourage consumers to accept parcel locker service.